Gender diversity on the board and firms' corporate social responsibility - Cristina Gaio; Tiago Cruz Gonçalves (International Journal of Financial Studies, 2022)
Corporate Social Responsibility (CSR) has progressively assumed a strategic role in corporate business. In this sense, the board of directors (Board) assumes a preponderant role, since they make decisions about business strategy. One considerably debated characteristic of Board diversity is gender, since women differ from men in terms of personality, communication style, and values. Therefore, this study analyzes the relationship between CSR and gender diversity on Boards, in a sample of European public firms. Results indicate that firms with a higher percentage of women in the Board have higher CSR practices, suggesting that the presence of women can play an important role in terms of CSR decisions, contributing to more social and sustainable firms. Results also suggest that management teams with a higher female percentage associate with better CSR scores, and firms that exhibit both a higher percentage of women on the Board and on the management team improve CSR scores. From an ethical perspective, more socially responsible firms present more trustworthy financial information, and more sustainable economic performance, which decreases risk assessment from their business partners and remaining stakeholders. Thus, results may be of interest to different stakeholders, such as policymakers, investors, and business partners, in order to increase firms' involvement in CSR.
Keywords: 330; board of directors; corporate social responsibility; Europe; gender diversity